2017
DOI: 10.1038/s41598-017-12707-7
|View full text |Cite
|
Sign up to set email alerts
|

NUMBL Interacts with TAK1, TRAF6 and NEMO to Negatively Regulate NF-κB Signaling During Osteoclastogenesis

Abstract: NF-κB signaling is essential for osteoclast differentiation and skeletal homeostasis. We have reported recently that NUMB-like (NUMBL) protein modulates osteoclastogenesis by down regulating NF-κB activation. Herein, we decipher the mechanism underlying this phenomenon. We found that whereas NUMBL mRNA expression decreases upon stimulation of wild type (WT) bone marrow macrophages (BMMs) with RANKL, TAK1 deficiency in these cells leads to increased NUMBL and decreased TRAF6 and NEMO expression. These changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…determined that NumbL promotes polyubiquitination of TRAF6 and NEMO in osteoclasts [38]. Overall, NumbL depletion seems to be beneficial for the survival of beta cells under diabetogenic conditions.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…determined that NumbL promotes polyubiquitination of TRAF6 and NEMO in osteoclasts [38]. Overall, NumbL depletion seems to be beneficial for the survival of beta cells under diabetogenic conditions.…”
Section: Discussionmentioning
confidence: 89%
“…TRAF6 activity depends on its polyubiquitination [16], and it is not clear if TRAF6, being an ubiquitin ligase, ubiquitinates itself or if other factors are involved [15,16,38]. Swarnker et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As NumbL downregulation inhibits NF-κB signaling under GLT, we evaluated the mechanism through which NumbL is linked to NF-κB. Several groups have reported that NumbL interacts with TRAF6 and modulates NF-κB signaling [ 30 , 31 ]. Thus, we tested the dynamics of the interactions between NumbL and TRAF6 under GLT conditions in beta cells.…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory reaction in MSCs-lung is likely due to the interaction of SARS-CoV-2 with TLRs, whose cascade culminates with the activation of NF-κB: upon activation, NF-κB translocates into the nucleus and binds to DNA to promote the transcription of different genes, proinflammatory cytokines among them. NUMBL , encoding for Numb-like protein, is known to be a negative regulator of NF-κB: in an experiment of osteoclastic differentiation, using cells isolated from the bone marrow of RElA-luc reporter mice, it was clear that NUMBL protein decreased RelA levels, a subunit of NF-κB, after RANKL treatment [ 43 ]. So, it is coherent to find NUMBL downregulated in MSCs-lung, where we suppose the activation of NF-κB, and found it upregulated in MSCs-CPAM, where there should not be activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%